Joint gravity and isostatic analysis for basement studies - A novel tool - BRAITENBERG, CARLA; Wienecke S.; Ebbing J.; Born W.; Redfield T. (EAGE-SEG, 2007)
We have created a working tool – named Lithoflex- that is useful for the interpretation of gravity data in oceanic and continental areas. The tool combines gravity forward and inverse calculation with an investigation of the isostatic state. Density models derived from the gravity field are ambiguous if external geological or geophysical constraints are scarce or unavailable. However, because isostasy is a physical condition , some of the native ambiguity can be reduced by checking the compatibility of the density model with the isostatic state. We demonstrate the usefulness of our tool in the analysis of the basement in the Barents Sea and in the South China Sea, where the basement characterization is accomplished by the high-resolution analysis of the equivalent elastic thickness. Other situations for which our tool could be useful include the recovery of depth-to-basement by the inversion of the gravity field, the identification of distinctive terrains by their variation in elastic thickness, or, given a comprehensive gravity field, the interpolation of crustal thickness between seismic lines.